Lack of evidence of viability and infectivity of SARS-CoV-2 in the fecal specimens of COVID-19 patients - Joshi, Madhuri; Mohandas, Sreelekshmy; Prasad, Sharda; Shinde, Manohar; Chavan, Nutan; Yadav, Pragya D.; Lavania, Mallika (Frontiers in Public Health, 2022)
SARS-CoV-2 can be shed in feces and can enter sewage systems. In order to implement effective control measures and identify new channels of transmission, it is essential to identify the presence of infectious virus particles in feces and sewage. In this study, we attempt to utilize Molecular techniques, cell cultures and animal models to find out the infectivity of SARS-CoV-2 in the feces of COVID-19 patients. Our findings exclude the presence of infectious virus particles, suggesting that fecal-oral transmission may not be the main mode of transmission. Larger-scale initiatives are nevertheless required, particularly considering the emergence of new viral strains.